The genus Pseumenes Giordani Soika, 1935 (Hymenoptera: Vespidae: Eumeninae) in the Philippine Islands, with description of a new species - Selis, Marco (Zootaxa, 2017)
A taxonomic study on the genus Pseumenes Giordani Soika, 1935, from the Philippine Islands is presented. A new species, Pseumenes azurescens Selis, sp. nov., is described. Pseumenes depressus palawanensis Giordani Soika, 1993, is raised to species rank (P. palawanensis stat. nov.). P. polillensis (Giordani Soika, 1941) is newly recorded from Luzon. A key to species of the genus from the Philippine Islands is provided.